Criminal Responsibility for Police Officers as Narcotics Dealers: Pertanggung Jawaban Pidana Terhadap Aparat Kepolisian Sebagai Pengedar Narkotika - Sitepu, Chechilia Winri Putri; Zulyadi , Rizkan; Frensh , Wenggedes (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The involvement of law enforcement officers in drug trafficking poses a serious threat to the credibility and integrity of the police institution. Specific Background: While the general public is subject to strict legal consequences for narcotics distribution, the role of police officers as offenders introduces a complex dynamic in the enforcement of narcotics law. Knowledge Gap: Existing studies often overlook the mechanisms and accountability processes specific to police officers involved in such crimes. Aim: This study aims to examine the legal regulations, legal procedures, and criminal liability applied to police officers who act as drug dealers.Results: Using a normative juridical method, the findings reveal that police officers are held criminally accountable under the Narcotics Law, without exception or special treatment. Legal proceedings are conducted in general courts, and offending officers are typically suspended and risk dishonorable discharge (PTDH) for institutional damage. Novelty: The research highlights the internal disciplinary implications in addition to formal legal sanctions, emphasizing institutional accountability. Implications: The study suggests the imposition of severe sanctions against offending officers to preserve public trust and institutional integrity, and to serve as a deterrent against abuse of authority in narcotics crimes. Highlights: Police officers face the same legal process as civilians for narcotics crimes. Offending officers are subject to suspension and possible dishonorable discharge. Harsh sanctions are essential to uphold public trust in law enforcement. Keywords: Criminal Liability, Police Officer, Drug Trafficking, Narcotics Law, Institutional Integrity